A striking new species of Prosoeca Schiner, 1867 (Diptera: Nemestrinidae): An important pollinator from the Bokkeveld Plateau, Northern Cape Province, South Africa - Barraclough, David. A.; Colville, Jonathan F.; Karolyi, Florian; Krenn, Harald W. (Zootaxa, 2018)
For more than 20 years an undescribed species of Prosoeca has been referred to in numerous publications by pollination biologists, evolutionary biologists and ecologists, originally as being part of the Prosoeca peringueyi Lichtwardt, 1920, pollination guild. Ongoing research in these and related fields has necessitated the formal description of this large-bodied, striking new species, with a proboscis 1.5–2.3 x body length (mean proboscis length ± SD 36.25 ± 3.90 mm). Prosoeca marinusi Barraclough sp. nov. is described from a long series from the Hantam National Botanical Garden, Nieuwoudtville, Bokkeveld Plateau, Northern Cape Province, South Africa. The species is a narrow-range endemic and is restricted to the Nieuwoudtville area. Observations on the biology of the species are also presented. Prosoeca marinusi Barraclough sp. nov. is the only or main pollinator of at least four plant species (all regional endemics) in the family Iridaceae that flower from August to September. During August, Lapeirousia oreogena Goldblatt and Babiana vanzyliae L. Bolus are the main host flowers, while later in the spring season, Babiana framesii L. Bolus is most abundant in the Nieuwoudtville area.